2014
DOI: 10.1111/cbdd.12466
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Cellulose Nanocrystals for Potential Application in Topical Delivery of Hydroquinone

Abstract: Nanotechnology-based drug delivery systems can enhance drug permeation through the skin and improve the drug stability. The biodegradability and biocompatibility of cellulose nanocrystals have made these nanoparticles good candidates to use in biomedical applications. The hyperpigmentation is a common skin disorder that could be caused by number of reasons such as sun exposure and pregnancy. Hydroquinone could inhibit the production of melanin and eliminate the discolorations of skin. This study is aimed at in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(54 citation statements)
references
References 24 publications
2
52
0
Order By: Relevance
“…Three categories of nanocellulose materials have been described as drug carriers: planar hydrogels (fleeces, films, membranes, coatings) [410][411][412][413], CNFs [414,415] as well as CNCs [416][417][418][419], with the two latter preferentially formulated as nano-and microparticles, gels, or suspensions [9]. For the entrapment of drugs these materials were used in the wet native [37,420,421], dried (freeze-dried, critical point dried) [422] or semi-dried [413,423] form, as well as air-dried materials with a shape memory effect [29,424].…”
Section: Figure 16mentioning
confidence: 99%
“…Three categories of nanocellulose materials have been described as drug carriers: planar hydrogels (fleeces, films, membranes, coatings) [410][411][412][413], CNFs [414,415] as well as CNCs [416][417][418][419], with the two latter preferentially formulated as nano-and microparticles, gels, or suspensions [9]. For the entrapment of drugs these materials were used in the wet native [37,420,421], dried (freeze-dried, critical point dried) [422] or semi-dried [413,423] form, as well as air-dried materials with a shape memory effect [29,424].…”
Section: Figure 16mentioning
confidence: 99%
“…Such a wide application spectrum is related mainly to their nanometer-sized features, large surface area, specific biomechanical characteristics, surface chemistry, ease of conjugation, high biocompatibility, and low (if any) cytotoxicity (Alexandrescu et al 2013) with tolerogenic potential to the immune system (Tomić et al 2016). Due to a general acceptance as˝biosafe˝nanomaterial (Č olić et al 2014;Tomić et al 2016), the cellulose nanocrystals (CNCs), with typical sizes of \300 nm in length and around 10 nm in diameter (Habibi et al 2010), have also been readily evaluated as catalysis (Zhou et al 2013) in biomedical engineering (Sinha et al 2015), as well as targeted drugs (Taheri & Mohammadi 2015) and gene (Hu et al 2015) delivery. Recent studies also demonstrated the potential of CNCs to target tumours via the Enhanced Permeability and Retention (EPR) effect and delivery of organic compounds or drugs into cancer cells (Drogat et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In this direction, another nanotechnology‐based drug delivery system designed (hydroquinone–CNC complex) inhibited the production of melanin and eliminated the discolorations of skin caused by sun exposure and pregnancy. The conjugate was prepared to enhance drug permeation through the skin and to promote sustained release (80% of bound hydroquinone was released in 4 h) …”
Section: Technological Potential Of Cncs: the Development Of A New Gementioning
confidence: 99%